2015
DOI: 10.3168/jds.2014-7976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of camelina oil or live yeasts (Saccharomyces cerevisiae) on ruminal methane production, rumen fermentation, and milk fatty acid composition in lactating cows fed grass silage diets

Abstract: The potential of dietary supplements of 2 live yeast strains (Saccharomyces cerevisiae) or camelina oil to lower ruminal methane (CH4) and carbon dioxide (CO2) production and the associated effects on animal performance, rumen fermentation, rumen microbial populations, nutrient metabolism, and milk fatty acid (FA) composition of cows fed grass silage-based diets were examined. Four Finnish Ayrshire cows (53±7 d in milk) fitted with rumen cannula were used in a 4×4 Latin square with four 42-d periods. Cows rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
90
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 52 publications
20
90
3
Order By: Relevance
“…Increases in CO decreased silage and total DMI by 27 and 18%, respectively, in the absence of changes in total-tract NDF digestibility. The magnitude of decreases in intake were higher compared with a recent report of a 12% decrease in DMI in response to inclusion of 60 g of CO/kg of DM that increased the FA content of a TMR based on grass silage from 22 to 77 g/kg of DM (Bayat et al, 2015). However, both the proportion of concentrate in diet DM (from 50 to 55%) and apparent total-tract OM digestibility (from 74 to 75%) were similar in this and the earlier report (50 and from 69 to 72%, respectively; Bayat et al, 2015).…”
Section: Dmimentioning
confidence: 52%
See 3 more Smart Citations
“…Increases in CO decreased silage and total DMI by 27 and 18%, respectively, in the absence of changes in total-tract NDF digestibility. The magnitude of decreases in intake were higher compared with a recent report of a 12% decrease in DMI in response to inclusion of 60 g of CO/kg of DM that increased the FA content of a TMR based on grass silage from 22 to 77 g/kg of DM (Bayat et al, 2015). However, both the proportion of concentrate in diet DM (from 50 to 55%) and apparent total-tract OM digestibility (from 74 to 75%) were similar in this and the earlier report (50 and from 69 to 72%, respectively; Bayat et al, 2015).…”
Section: Dmimentioning
confidence: 52%
“…The magnitude of decreases in intake were higher compared with a recent report of a 12% decrease in DMI in response to inclusion of 60 g of CO/kg of DM that increased the FA content of a TMR based on grass silage from 22 to 77 g/kg of DM (Bayat et al, 2015). However, both the proportion of concentrate in diet DM (from 50 to 55%) and apparent total-tract OM digestibility (from 74 to 75%) were similar in this and the earlier report (50 and from 69 to 72%, respectively; Bayat et al, 2015). The larger decrease in DMI to CO in the present experiment might have been related to the inclusion in concentrates fed separately at specified time points, leading to a more sudden release of unsaturated FA in the rumen compared with adding CO as part of a TMR (Bayat et al, 2015).…”
Section: Dmimentioning
confidence: 52%
See 2 more Smart Citations
“…The SF 6 technique has been used to estimate CH 4 emission using samples of rumen gas, rather than breath samples (Bayat et al, 2015), however Beauchemin et al (2012) recommended against the use of the SF 6 technique in rumen cannulated animals. Beauchemin et al (2012) concluded that the rumen cannulae would need to be tight fitting to minimize gas leakage, and more animals would be required to overcome additional variability.…”
Section: )mentioning
confidence: 99%